Biohuertos Hortícolas para Sectores Rur- urbanos. - Díaz Mayorga, Héctor Alexander (2022)
Horticultural Bio-gardens for Rur-urban Sectors, it is of the utmost importance to create Horticultural Bio-gardens with the intention of harvesting vegetables organically to generate a good for the population's health. Through this activity we can encourage more people or families to be part of this, giving professional training that we can encourage to create their own bio-gardens with ecological methods to care for and preserve the soil without being infertile, government entities are also participants in this, providing adequate instruments for the work. Over the centuries, orchards have been adapting to the specific climate conditions of each region and the type of soil. It is an important work of agronomic craftsmanship, the orchards have selected thousands of different varieties of orchard plants all over the world, they have perfected cultivation systems, they have learned to reduce, recycle and use long before it was a maxim of waste generation, have taken the best of their soils without degrading them and have taken advantage of every last drop of water. The objects of study of the orchard are contemplated from the area of natural sciences and can range from the study of the plant organization model and its diversity, autotrophic nutrition, interactions with the physical environment (water, soil, climate). The distribution and abundance of organisms and changes in individuals, populations and the ecosystem, pests, biological control; human-induced impacts: pollution; soil degradation, etc. In the fertilization of the orchards, the fertilizers that were used were organic, which are found in all material that comes from organic sources, such as vegetable stubble, plants and their derivatives (trunks, branches, stems, leaves, flowers, etc.). Pest insects, diseases and crop weeds do not constitute a major problem in this type of orchard, because a biological balance is established in them, attributable to the organic preparation of the soil, crop rotation that is practiced, and the influence of plants. companions and, in general, to the diversity of plants and animal species that are kept inside.